Hubungan Beberapa Faktor dengan Tingkat Endemisitas DBD di Puskesmas Dlingo I Bantul Tahun 2008 - Daryati Prihatin Achmad; Heru Subaris Kasjono; Achmad Husein (Sanitasi: Jurnal Kesehatan Lingkungan, 2008)
Dengue Haemorrhagic Fever (DHF) is one of the major health problem in the period of 2005 to 2025. Therefore, it is urgent to find the ways to solve this problem as so many people got this disease every year. The purpose of the research was aimed to reveal the relationship between the knowledge level of DHF disease, the action level of DBD controlling as well as the existence of the corresponding Aedes aegypti larvae, with the endemicity level in the Dlingo I Community Health Centre. The study employed survey method with cross sec-tional approach in two villages i.e. Dlingo and Mangunan which represents en-demic and sporadic areas respectively. The interviewed respondent of this stu-dy was housewives and the data needed were collected by using questionnaire and also checklist to observe the mosquitos. By conducting chi square and pearson correlation test, the study concluded that endemicity was not cor-related with knowledge level (p-value 0,164). However, the endemicity were associated with both the controlling action (p-value 0,029) and the mosquito existency (p-value 0,001). Based on this findings, in order to prevent the occurence of DBD in the future, it was suggested that people have to re-vitalize the 3M program and the eradication of the mosquitoes’ breeding places. It was advised as well for DBD control counsellor to improve and to increase the health education program and to organize people who responsible in observing the existence of mosquito larvae amongst the community.